Productivity and unemployment : an ABM approach - Fernández-Márquez, Carlos Manuel. (2020)
We investigate the relationship between productivity and unemployment with an ABM approach. In particular, we use the framework of Riccetti et al. (2015) to run computer simulations considering different levels of productivity and analyse the corresponding effects on unemployment. The simulation results show the emergence of a fluctuating pattern of the unemployment rate, the public deficit and the inflation rate as functions of productivity. The marked pattern of the unemployment rate in the model is empirically validated by the OECD database. This unexpected oscillating behaviour remains in subsequent simplifications of the baseline model. Thus, our approach allows us to explain the productivity-employment linkage as an emergent macroeconomic property of a complex system. We conclude that economic policies aimed at increasing labour productivity could have unintended side effects on the unemployment rate, the government deficit and the inflation rate, which should be explored and taken into account before the policy is implemented.